Methods of Using Artificial Intelligence in Insurance Companies and its Promising Directions - Zakirxodjaeva, Sh. A. (Research Parks Publishers, 2023)
This article highlights and substantiates the methods of using artificial intelligence in the effective organization of the activities of insurance organizations and in order to reduce excessive costs, convenience and prospects of maintaining an insurance portfolio in electronic form.